Determination of the exercise intensity that elicits maximal fat oxidation - Achten, J.; Gleeson, M.; Jeukendrup, A. E. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The aim of this study was to develop a test protocol to determine the exercise intensity at which fat oxidation rate is maximal (Fatmax). METHOD: Eighteen moderately trained cyclists performed a graded exercise test to exhaustion, with 5-min stages and 35-W increments (GE35/5). In addition, four to six continuous prolonged exercise tests (CE) at constant work rates, corresponding to the work rates of the GE test, were performed on separate days. The duration of each test was chosen so that all trials would result in an equal energy expenditure. Seven other subjects performed three different GE tests to exhaustion. The test protocols differed in stage duration and in increment size. Fat oxidation was measured using indirect calorimetry. RESULTS: No significant differences were found in Fatmax determined with the GE35/5, the average fat oxidation of the CE tests, or fat oxidation measured during the first 5 min of the CE tests (56 +/- 3, 64 +/- 3, 58 +/- 3%VO2max, respectively). Results of the GE35/5 protocol were used to construct an exercise intensity versus fat oxidation curve for each individual. Fatmax was equivalent to 64 +/- 4%VO2max and 74 +/- 3%HRmax. The Fatmax zone (range of intensities with fat oxidation rates within 10% of the peak rate) was located between 55 +/- 3 and 72 +/- 4%VO2max. The contribution of fat oxidation to energy expenditure became negligible above 89 +/- 3%VO2max (92 +/- 1%HRmax). When stage duration was reduced from 5 to 3 min or when increment size was reduced from 35 to 20 W, no significant differences were found in Fatmax, Fatmin, or the Fatmax zone. CONCLUSION: It is concluded that a protocol with 3-min stages and 35-W increments in work rate can be used to determine Fatmax. Fat oxidation rates are high over a large range of intensities; however, at exercise intensities above Fatmax, fat oxidation rates drop markedly.